Investigation of Crohn's disease risk loci in ulcerative colitis further defines their molecular relationship. - Anderson, C; Massey, D; Barrett, J; Prescott, N; Tremelling, M; Fisher, SA; Gwilliam, R; Jacob, J; Nimmo, E; Drummond, H; Lees, C; Onnie, C; et al. (2009)
BACKGROUND and AIMS: Identifying shared and disease-specific susceptibility loci for Crohn's disease (CD) and ulcerative colitis (UC) would help define the biologic relationship between the inflammatory bowel diseases. More than 30 CD susceptibility loci have been identified. These represent important candidate susceptibility loci for UC. Loci discovered by the index genome scans in CD have previously been tested for association with UC, but those identified in the recent meta-analysis await such investigation. Furthermore, the recently identified UC locus at ECM1 requires formal testing for association with CD. METHODS: We analyzed 45 single nucleotide polymorphisms, tagging 29 of the loci recently associated with CD in 2527 UC cases and 4070 population controls. We also genotyped the UC-associated ECM1 variant rs11205387 in 1560 CD patients and 3028 controls. RESULTS: Nine regions showed association with UC at a threshold corrected for the 29 loci tested (P < .0017). The strongest association (P = 4.13 x 10(-8); odds ratio = 1.27) was identified with a 170-kilobase region on chromosome 1q32 that contains 3 genes. We also found association with JAK2 and replicated a recently reported association with STAT3, further implicating the role of this signaling pathway in inflammatory bowel disease. Additional novel UC susceptibility genes were LYRM4 and CDKAL1. Twenty of the loci were not associated with UC, and several appear to be specific to CD. ECM1 variation was not associated with CD. CONCLUSIONS: Collectively, these data help define the genetic relationship between CD and UC and characterize common, as well as disease-specific mechanisms of pathogenesis.